2017
DOI: 10.1142/s0217751x17501810
|View full text |Cite
|
Sign up to set email alerts
|

Six indications of radical new physics in supernovae Ia

Abstract: After more than forty years since the basic standard model for supernovae Ia (SN Ia) was proposed many astronomers are still hopeful that this phenomenon will ultimately be understood in terms of Newtonian gravity plus nuclear and particle physics as they existed in the 1930's. In spite of this fact there are at least six nagging puzzles in supernovae physics that suggest some radical new physics input may be necessary. "Radical" in this context means a physics idea that did not exist in the 1930's and that is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 29 publications
1
4
1
Order By: Relevance
“…In contradistinction to the binary models we have noted [3] that there are at least six major indications that SN Ia may be due not to mass growth to the Chandrasekhar maximum but, instead, to a phase transition in a possibly isolated white dwarf. Some years ago, Sim et al [4] showed that, if a suitable trigger could be found, the detonation of an isolated white dwarf with mass between 0.97 and 1.15 could lead to good agreement with observed SN Ia properties.…”
Section: Introductioncontrasting
confidence: 62%
See 4 more Smart Citations
“…In contradistinction to the binary models we have noted [3] that there are at least six major indications that SN Ia may be due not to mass growth to the Chandrasekhar maximum but, instead, to a phase transition in a possibly isolated white dwarf. Some years ago, Sim et al [4] showed that, if a suitable trigger could be found, the detonation of an isolated white dwarf with mass between 0.97 and 1.15 could lead to good agreement with observed SN Ia properties.…”
Section: Introductioncontrasting
confidence: 62%
“…These separate energies are calculated in ref. [3] and elsewhere. For instance, as treated there, E kin = 5.6 10 −4 (1.22M ⊙ + 0.2M) .…”
Section: The Delay Time and Ejected Mass Distributionsmentioning
confidence: 99%
See 3 more Smart Citations